Effect of the riparian forest on the fish community of the Tumbaro, Naranjillo and Mayo rivers in the shampuyacu native community, Awajun, Peru - Torres Zevallos, Uriel Arnaldo (2023)
The objective of this research is to determine the effect of the riparian forest on the fish community of the Tumbaro, Naranjillo, and Mayo rivers in the Native Community of Shampuyacu, Awajun, Peru. Sampling was carried out at 14 points in the three rivers located in the Native Community. The collection of fish involved the use of passive and active fishing gear. The riparian forest was classified utilizing satellite images into three categories: primary forest, secondary forest, and agricultural cultivation, and finally eight physicochemical parameters were measured. A total of 1,198 fishdistributed in 12 families and 27 species were collected. The Characiformes represented 57.3% of the total, followed by the Siluriformes (32.7%) and Perciformes (10%). Chaetostoma marmorescens Eigenmann & Allen, 1942, Chaetostoma sp. (Tschudi, 1846), and Hypostomus fonchii (Weber & Montoya-Burgos, 2002) were the three most abundant specieswith 7.33 %, 6.90 %, and 4.37 %, respectively. The Tumbaro River presented the highest species richness (S) with 23 species, followed by the Naranjillo River (S = 21) and the Mayo River (S = 18). The specific richness (S), the Shannon- Wiener index (H’), and the Simpson index (D) were different between the points categorized as agricultural and primary forests; while the points considered as secondary forests were not different from primary forests, and with agricultural cultivation. Physicochemical parameters such as temperature and ammonium had a significant positive effect on H’, while nitrate and conductivity had a significant negative effect. It is concluded that the disturbance of the riparian forest has a significant effect on the diversity of fish in the Tumbaro, Naranjillo, and Mayo rivers in the Native Community of Shampuyacu, Awajun, Peru.